The impact of multilayer subcontracting system in construction industry in Pahang - Nasyrah Fahada, Abdul Razak (2013)
In construction industry, there is possibility for subcontractors to sublet their work to other subcontractors. It called multilayer subcontracting. Multilayer subcontracting has been identified as a source of poor time performance of projects in previous study. This study is about the impact of multilayer subcontracting system on project performance in Malaysian construction industry. The purpose of this paper is to study how multilayer subcontracting practice impacts the project time performance. It provides a perspective that multilayer subcontract could address the poor time performance caused by multilayer subcontracting. From previous study it shows that the multilayer subcontracting practice can be divided into five areas, which are communication, cost control, labour force, worker safety and productivity. This study expecting a positive relationship between multilayer subcontracting practices and project time performance. A method of survey questionnaire is being used in order to collect the data. The questionnaire distributed to contractor with “A” class registered with local authority, Pusat Khidmat Kontraktor (PKK). There are three sections in the questionnaire; Section A: Demography; Section B: Are they practice multilayer subcontracting; Section C; Their performance in time management. 84 respondents were targeted however only 52.38% gave feedback. The collected data was analysed using Statistical Package for the Social Science. This study found that there are only two areas that have positive relationship with the time performance namely worker safety and productivity. However it shows that the contractors actively practice multilayer subcontracting in the area of labour force.